The role of endothelial junctions in the regulation of the extravasation of tumor cells. A historical reappraisal - Ribatti, Domenico (Frontiers in Oncology, 2024)
Endothelial cells lining the vessel wall are connected by adherents, tight and gap junctions. Adherent junctions are common to all endothelial cells, whereas tight and gap junctions graduate within different vascular segments. Endothelial cell-cell junctions sustain vascular homeostasis and to control the transendothelial migration of inflammatory cells. Tumor cells need to weaken endothelial cell-cell junctions to penetrate the endothelial barrier and transendothelial migration and metastasis of tumor cells are tightly controlled by endothelial cell-cell junctions.